2016
DOI: 10.1007/s10965-016-1042-1
|View full text |Cite
|
Sign up to set email alerts
|

Poly (vinyl alcohol)/chitosan cryogels as PH responsive ciprofloxacin carriers

Abstract: The pH responsiveness of swelling behavior and the release of ciprofloxacin hydrochloride from poly (vinyl alcohol)/chitosan cryogels of various compositions were investigated. All cryogels swelled and reached equilibrium within 100 min, indicating that the cryogels swell relatively fast. Increasing the chitosan content in the poly (vinyl alcohol) cryogels increased the swelling capacity of the cryogels. The poly (vinyl alcohol)/chitosan cryogels exhibited a sudden change in swelling characteristics at a certa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 46 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…The variation of the kinetic parameter values is asociated with the p K a values of the components and their interactions by functional groups, as was demonstrated for other pH-responsive systems [ 62 , 63 , 64 , 65 , 66 ], and in this case those of MTX and HA.…”
Section: Resultsmentioning
confidence: 52%
“…The variation of the kinetic parameter values is asociated with the p K a values of the components and their interactions by functional groups, as was demonstrated for other pH-responsive systems [ 62 , 63 , 64 , 65 , 66 ], and in this case those of MTX and HA.…”
Section: Resultsmentioning
confidence: 52%
“…Zupanc ˇic ˇet al 14 reported that thicker nanofibers can reduce the bacterial cell mobility more profusely and quickly than thinner fibers as the response was cell-line specific. 15,16 Therefore, nanofibers can exhibit strong inhibition performance and be used as antibacterial agents 17,18 in drug delivery, 19,20 tissue engineering, [21][22][23] bio-adhesive, 20 and filtration.…”
Section: Introductionmentioning
confidence: 99%